2021
DOI: 10.4103/jmas.jmas_3_20
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic sleeve gastrectomy

Abstract: Setting: Laparoscopic sleeve gastrectomy (LSG) is gaining popularity as a bariatric option. Gastric leak (GL) is the most dreaded septic complication of LSG. Early detection and treatment of this complication may improve outcomes. Objectives: This study investigates biomarkers that might be useful to predict GL before its clinical presentation in patients who underwent LSG. Patients and Methods: This study, prospective observational, was carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…From the univariant analysis in this study, we found that CRP on POD 4 achieved optimal AUROC of 0.857 with a cutoff value of 159.5 (Figure 2). This result echoed afar with numerous researches recently [27][28][29][30][31] , suggesting that CRP was one of the most commonly used and widely verified clinical predictors for postoperative AL and other postoperative infections. Other variables presenting great potential include NLR on POD 4 (AUROC=0.802, cutoff value=10.55), minimum serum albumin during hospitalization (AUROC=0.7475, cutoff value=32.25) (Figure 2), which also indicated that poor overall immunonutritional internal environment may increase risk of postoperative AL.…”
Section: Discussionmentioning
confidence: 56%
“…From the univariant analysis in this study, we found that CRP on POD 4 achieved optimal AUROC of 0.857 with a cutoff value of 159.5 (Figure 2). This result echoed afar with numerous researches recently [27][28][29][30][31] , suggesting that CRP was one of the most commonly used and widely verified clinical predictors for postoperative AL and other postoperative infections. Other variables presenting great potential include NLR on POD 4 (AUROC=0.802, cutoff value=10.55), minimum serum albumin during hospitalization (AUROC=0.7475, cutoff value=32.25) (Figure 2), which also indicated that poor overall immunonutritional internal environment may increase risk of postoperative AL.…”
Section: Discussionmentioning
confidence: 56%
“…Many studies have shown that inflammatory scores can improve the accuracy of complication prediction after bariatric surgery [21][22][23][24]. The determination of amylase in the drain liquid apparently may be an inexpensive and easily available tool (in the same way as inflammatory markers) to help in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…This endoscopic approach has several potential advantages [ 22 ], including its minimally invasive nature, lack of influence of BMI, and the minimal inflammation produced by the procedure, which does not interfere with the healing process [ 23 ].…”
Section: Discussionmentioning
confidence: 99%